76.7k views
2 votes
Which expression is equivalent to 19 - 27 a. 27 - 19 b. -19 + 27 c. 19 + -27 d. -19 + 27

User Whoacowboy
by
5.7k points

2 Answers

5 votes

Answer:

c.19 + -27

Explanation:

you do kcc (keep change change) and you keep the first number flip the sign and then change the positive 2 a negative

User Matatk
by
7.9k points
2 votes

Answer:

c. 19 + -27

Explanation:

We know:

a - b = a + (-b)

a + b = b + a

19 - 27 = 19 + (-27) = (-27) + 19 = -27 + 19

User ZillGate
by
7.0k points